POLITIK IDENTITAS MASYARAKAT PERBATASAN INDONESIA-MALAYSIA: KASUS BADAU DI KAPUAS HULU, KALIMANTAN BARAT - Irwan Abdullah dan Intan Pemata Sari (Universitas Gadjah Mada, 2014)
Border area studies has become extremely important since the state border creates tensions of sovereigntyand identity in relations between Indonesia and ten other neighboring countries. Border area cannotperceive as only a neutral area without any meanings as it becomes a mirror of the nation since it is theentrance for the coming of people and goods from other countries. The border area therefore is not onlya statement of the administrative line of the country that is influential for the sovereignty, but also ofthe cultural line to stress identity. This article shows that administrative-political border which dividesDayak Iban become two parts has also created the tension between state-society in the border area, as thenationalism has to face the distressed ethnic identities. Dual existence of the ethnic group is influential onthe maintenance of identity and nationalism of the border community, which shows a challenge to therole of the state. Moreover, the living condition of Dayak Iban in Badau is in contrast to the Dayak Ibanin Lubok Antu, which is more prosperous. The fact that the people in the border area live in scarcity,adversity, and inadequate has delegitimated the state existence that challenges the national identity. Thesituation has produced the fact that people of Badau perform three identities: as a border society (politics),as part of the Iban community (cultural), and as part of global society (economy). The findings sharpenFoote and Burke’s theory by presenting that identity is not only determined by the structural relations, butalso developed through contested process where the actors also produce meanings to state their existence.